2014
DOI: 10.1155/2014/928579
|View full text |Cite
|
Sign up to set email alerts
|

Si‐Jun‐Zi Decoction Treatment Promotes the Restoration of Intestinal Function after Obstruction by Regulating Intestinal Homeostasis

Abstract: Intestinal obstruction is a common disease requiring abdominal surgery with significant morbidity and mortality. Currently, an effective medical treatment for obstruction, other than surgical resection or decompression, does not exist. Si-Jun-Zi Decoction is a famous Chinese medicine used to replenish qi and invigorate the functions of the spleen. Modern pharmacological studies show that this prescription can improve gastrointestinal function and strengthen immune function. In this study, we investigated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…Glycyrrhizae mediates the property of prescriptions as the Guiding drug (Jia et al, ). According to clinical studies performed over the past few decades, SJZD has been used to treat patients with chronic gastritis or chronic atrophic gastritis, nausea, vomiting and diarrhoea (Liu, Yang, & Cai, ; Yu et al, ). Moreover, SJZD has been shown to control tumor progression, prolong patients’ lives, improve their quality of life (Guo & Zhang, ), prevent recurrence and metastasis in postoperative patients (Huang, Xi‐Hua, & Chen, ; Liang, Zhang, & Cai, ), and exert potential effects on immune system activation (Liu et al, ) and tumor therapy (Wu & Xuan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Glycyrrhizae mediates the property of prescriptions as the Guiding drug (Jia et al, ). According to clinical studies performed over the past few decades, SJZD has been used to treat patients with chronic gastritis or chronic atrophic gastritis, nausea, vomiting and diarrhoea (Liu, Yang, & Cai, ; Yu et al, ). Moreover, SJZD has been shown to control tumor progression, prolong patients’ lives, improve their quality of life (Guo & Zhang, ), prevent recurrence and metastasis in postoperative patients (Huang, Xi‐Hua, & Chen, ; Liang, Zhang, & Cai, ), and exert potential effects on immune system activation (Liu et al, ) and tumor therapy (Wu & Xuan, ).…”
Section: Introductionmentioning
confidence: 99%
“…), has demonstrated effects of invigorating Qi and strengthening the spleen. Sijunzi decoction not only reduces intestinal mucosal injury and promotes the recovery of intestinal function but also improves the adaptive immune function after surgery [78]. A previous clinical study has shown that treatment with Sijunzi decoction for 3 days can further promote the recovery of gastrointestinal function of patients after laparoscopic gallbladder surgery [79].…”
Section: Sijunzi Decoctionmentioning
confidence: 99%
“…Intestinal obstruction causes failure of the intestine functions, leading to an increase of intestinal toxins, high intestinal pressure, bacterial translocation and malnutrition (1). Consequently, intestinal obstruction will affect the immune system (4). After intestinal obstruction repair, patients might still have nutritional deficiency and compromised immune function.…”
Section: Introductionmentioning
confidence: 99%
“…Sijunzi decoction is a traditional Chinese medicine that has been used for treatment of other diseases in previous studies as it has no side effects and it has a pharmacological effect in gastrointestinal function, immune system, ulcers and tissue repair (4,7,8). Sijunzi decoction, which is also known as the “Four Gentlemen” decoction, consists of four types of herbs: Poria cocos , Radix ginseng , Glycyrrhiza uralensis and Atractylodes macrocephala (9).…”
Section: Introductionmentioning
confidence: 99%